A dynamic search pattern motion estimation algorithm using prioritized motion vectors. Issue 8 (November 2016) - Amirpour, Hadi; Mousavinia, Amir
Abstract Motion estimation is one of the critical parts in video compression standards with a high computational load. Many motion estimation algorithms have been developed to reduce the number of search points compared to a full-search algorithm without losing the quality considerably. Most of them use fixed search patterns in their first step which may suffer from trapping into local minima or searching unnecessary blocks due to inappropriate size and type of search patterns. In this paper, a new dynamic search pattern using motion vectors of spatial and temporal neighboring blocks is proposed. The motion vectors of neighboring blocks are prioritized, in order to efficiently use of halfway stop technique. The simulation results indicate that proposed algorithm is very close to the full-search algorithm in quality, compared to other rivals. Moreover, the average number of searches is often less than other algorithms.